2‐Arylindoles: A New Entry to Transition Metal‐free Synthesis of 2‐Aminobenzophenones. (19th May 2016) - Yu, Jin; Moon, Hye Ran; Min, Beom Kyu; Kim, Jae Nyoung
Abstract : Various 2‐aminobenzophenones were synthesized from readily available 2‐arylindoles in DMSO under O2 balloon atmosphere. The synthesis was carried out without the aid of a transition metal catalyst or moisture‐sensitive organometallic reagents from 2‐arylindoles. Abstract :